Design a Case Based Reasoning Model for Design of Roller Bearing - Verma, Ashwani (Thapar Institute of Engineering and Technology, 2005)
Due to rising demand for automatic and semiautomatic devices and systems, roller bearing designing become an important task for the design engineer. Bearings are standard mechanical elements that play a very important role in design and are used extensively in a wide array of mechanical artifacts. Designing any thing from the scratch, is not an intelligent task in this fast running world, as we have learned a lot from the past experiences of the roller bearing design, what points should be considered while designing roller bearing and with what weightage? But for the human being to remember all the past experiences or seeking help from the expert people always not possible. To overcome this we use Artificial Intelligence's technique case based reasoning for design ( which comes under the computer aided design and manufacturing) which uses case representation or knowledge representation, case retrieval, case adaptation etc using computers because for computers the tasks like data storage, data retrieval, analysis are the mundane tasks for computers as compared to humans.
Keywords: Roller Bearing; Design Model; CAD; CAM; Robotics; Ball Bearing